Covert action failure and fiasco construction: William Hague’s 2011 Libyan venture - Cormac, Rory; Daddow, Oliver J. (Taylor & Francis, 2017)
In 2011 William Hague, then British Foreign Secretary, authorized a Special Forces team to enter Libya and attempt to contact rebels opposed to Muammar Gaddafi in the unfolding civil war. However, its members were detained by the rebels, questioned and ejected from the country. This article puts the literature on public policy failures into dialogue with that on covert action as a tool of foreign policy. It asks: why did this not develop into a fully-fledged policy fiasco when journalists and politicians alike judged it to have been a major error of judgement on Hague’s part? Using narrative analysis of the contemporary reporting of this incident, we argue that the government – possessing the advantage of information asymmetry accruing from operational secrecy – was ultimately able to win the battle of narratives in a frame contestation process. The study of information asymmetry can enhance the recently revivified research into foreign policy failures.